Knowing Me, Knowing You? Similarity to the CEO and Fund Managers' Investment Decisions - Stefan Jaspersen; Peter Limbach (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This study provides evidence that investors' demographic similarity to CEOs affects their investment decisions. We find that mutual fund managers overweight firms led by CEOs who resemble them in terms of age, ethnicity and gender. This finding is robust to excluding educational and local ties and is supported by variation in similarity caused by CEO departures. Investing in firms run by similar CEOs, on average, is associated with superior performance and is more pronounced when CEOs have more impact on their firms. Results suggest that demographic similarity to CEOs facilitates informed trading, implying that investors' information production incorporates firm management.
Keywords: G11; G23; J10; 330; CEO-investor similarity; familiarity bias; information advantages; investment decisions; mutual fund performance